Transformational Leadership, Information System, Supplier Integration and Supply chain performance: Examining the mediating role of Trust - Chairit Thongrawd; Nutchanat Meesompuch; Nuchjaree Pakasat; Naris Penpokai (International Journal of Supply Chain Management, 2020)
Abstract- The main purpose of the current paper is to examine impact of information system, supplier integration and transformational leadership on supply chain performance. Moreover, mediating role of trust is examined as well. For the present research study, the data was gathered from the employees of mining industry of Indonesia. The response rate of the study was 42.3%. Partial Least Square Structural Equation Modeling (PLS-SEM) technique is used for data analysis, following linearity, autocorrelation, non-multicollinearity and homoscedasticity assumptions, to ascertain whether underlying technique meets all the required assumptions. Information system and supplier integration do not impact significantly to the trust. Whereas the mediation of supplier integration, trust and supplier performance is reported insignificant. All other hypothesis is found significant. The findings of the study are important for the practitioner and policy makers of human resource and supply chain department of the organization.